Association between Serum Lactate Dehydrogenase Level and 30-day Mortality in Patients with Intracranial Hemorrhage with Acute Leukemia in the Induction Phase: A Cohort Study - Zhang, Jia-Yuan; Yan, Zhang-Song; Sun, Xiu-Juan; Liu, Yong-Ze; Yin, Yan-Ke; Su, Ming-Huan; Li, Qiu-Ling; Mi, Ying-Chang; Li, Da-Peng (Global Medical Genetics, 2024)
Objectives This study aimed to identify the association between lactate dehydrogenase (LDH) levels and 30-day mortality in patients with intracranial hemorrhage (ICH) with acute leukemia during the induction phase.Methods This cohort study included patients with acute leukemia with ICH during induction. We evaluated serum LDH levels upon admission. Multivariable Cox regression analyzed the LDH 30-day mortality association. Interaction and stratified analyses based on factors like age, sex, albumin, white blood cell count, hemoglobin level, and platelet count were conducted.Results We selected 91 patients diagnosed with acute leukemia and ICH. The overall 30-day mortality rate was 61.5%, with 56 of the 91 patients succumbing. Among those with LDH levels ≥ 570 U/L, the mortality rate was 74.4% (32 out of 43), which was higher than the 50% mortality rate of the LDH < 570 U/L group (24 out of 48) (p = 0.017). In our multivariate regression models, the hazard ratios and their corresponding 95% confidence intervals for Log2 and twice the upper limit of normal LDH were 1.27 (1.01, 1.58) and 2.2 (1.05, 4.58), respectively. Interaction analysis revealed no significant interactive effect on the relationship between LDH levels and 30-day mortality.Conclusions Serum LDH level was associated with 30-day mortality, especially in patients with LDH ≥ 570 U/L.
Keywords: lactate dehydrogenase; intracranial hemorrhage; acute leukemia